Early skewed differentiation and PD-1 expression in CD4+ cells relate to immune dysfunction and viral persistence in individuals living with HIV 1 year post-cART initiation - Salido, Jimena Patricia (2019)
Achieving HIV functional cure is a priority. Strategies such as adoptive cell transfer have been assayed, without success yet mainly due to immune dysfunctions observed among individuals. Samples from 25 HIV+ subjects were collected at diagnosis (baseline sample, BSL) and one year post-cART initiation (post- cART ). At BSL, bulk and HIV-specific CD4 phenotype (CD45RO , CCR 7, CD95 and PD1 expression) was assessed by flow cytometry after a short stimulation with HIV peptides. Also, proportion of CD4+/HLA-DR+/ CD38+ cells was measured. At post-cART , HIV-specific CD8TC s were obtained after 2-week expansion with peptides. Phenotype and antiviral activity (VIA and VITA L assays) were evaluated post-expansion. Plasma CXCL10 (IP-10) was assessed by ELISA. Cell-associated HIV DNA (total and integrated) and unspliced (US) and multiply-spliced (MS) RNA were quantified by real-time PCR. Non-parametric statistics were applied. Early CD4TC exhaustion, elevated activation and inadequate differentiation seem to be associated with viral persistence, inflammation, as well as with the phenotype and antiviral capacity of HIV-specific CD8TC s that persist one year after cART is initiated. These parameters could serve as predictors of CD8TC function on treated subjects.